2019
DOI: 10.1111/jocn.14843
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nursing organisational culture on face‐to‐face bullying and cyberbullying in the workplace

Abstract: Aims and objectives To investigate the current state of face‐to‐face bullying and cyberbullying among nurses in the workplace and to identify the effects of nursing organisational culture on face‐to‐face bullying and cyberbullying. Background It is important to accurately examine the current state of workplace bullying to acknowledge the gravity of the situation faced by nurses and devise prevention strategies. Electronic communication by computer or smartphone is widely used as a prompt and efficient means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Prevention, through various strategies, is essential to avoid transforming new graduates into new perpetrators of horizontal violence. 35 Unlike other studies, 9,19 no physicians, patients or their families were reported to use violence, but only as witnesses of episodes of violence, especially verbal abuse.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Prevention, through various strategies, is essential to avoid transforming new graduates into new perpetrators of horizontal violence. 35 Unlike other studies, 9,19 no physicians, patients or their families were reported to use violence, but only as witnesses of episodes of violence, especially verbal abuse.…”
Section: Discussionmentioning
confidence: 85%
“…To stem this phenomenon, its existence should already be explained to nursing students during the undergraduate programme to facilitate the prevention of workplace violence. 12,35 Prevention is also implemented through authentic leadership practices. 28,32 More attention must be given to the important role of mentorship, 19 on providing protected and compulsory coaching in all facilities, informing new graduates about reporting tools and to whom they can refer to whenever horizontal violence occurs, with the proactive support of the top management of the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Workplace cyberbullying was significantly correlated with perceived organizational support, turnover intention, and symptom experience 26 . In another study by Choi and Park, 27 the state of face‐to‐face bullying or cyberbullying in a Korean hospital were explored as they related to workplace culture. Nursing organizational culture resulted in 4.3% of cyberbullying cases ( N = 226), while a relation‐oriented culture was also a key factor 27 …”
Section: Definitions and Uses Of Conceptmentioning
confidence: 99%
“…Among the organizational factors, job stress, dissatisfaction, and suppressed anger may be expressed negatively toward coworkers (Choi & Park, 2019; Yun & Kang, 2014). Further, workplace cyberbullying is significantly related to ill health and job satisfaction among victims (Farley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%